2018
DOI: 10.1002/smll.201801967
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Shrinkable Nanotubes for Duplex Formation of Short Nucleotides

Abstract: Molecular monolayer nanotubes produced by self-assembly of an amphiphile modified with a 2-nitrobenzyl group as a photoresponsive unit are able to encapsulate dinucleotides via electrostatic attraction. Upon photoirradiation, the 18 nm inner diameter of the nanotubes shrinks to less than 2 nm as a result of photochemical cleavage of the 2-nitrobenzyl group in the amphiphile. This shrinking of the nanotube channels leads to a propulsive release of the dinucleotides into the bulk solution and simultaneously acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…For example, conjugated polymers that exist as random coils in bulk solution take on a 1D extended conformation in nanotubes with narrow channels, whereas the polymers take on an aggregated conformation in wider nanotube channels . In addition, supramolecular nanotubes can not only stabilize the native structures of proteins and double‐stranded DNA under harsh conditions but also accelerate refolding of denatured proteins and formation of oligonucleotide duplexes . However, synthesis of polymers inside nanotube channels has rarely been reported, although nanotubes have been widely utilized as templates for the construction of inorganic and metal nanostructures through sol–gel reactions and reduction of inorganic precursors and metal ions adsorbed on the surfaces of and/or encapsulated in the channels of the nanotubes …”
Section: Introductionmentioning
confidence: 99%
“…For example, conjugated polymers that exist as random coils in bulk solution take on a 1D extended conformation in nanotubes with narrow channels, whereas the polymers take on an aggregated conformation in wider nanotube channels . In addition, supramolecular nanotubes can not only stabilize the native structures of proteins and double‐stranded DNA under harsh conditions but also accelerate refolding of denatured proteins and formation of oligonucleotide duplexes . However, synthesis of polymers inside nanotube channels has rarely been reported, although nanotubes have been widely utilized as templates for the construction of inorganic and metal nanostructures through sol–gel reactions and reduction of inorganic precursors and metal ions adsorbed on the surfaces of and/or encapsulated in the channels of the nanotubes …”
Section: Introductionmentioning
confidence: 99%
“…Adding an equivalent of NaOH to a hydrochloride solution of 9 resulted in the formation of nanotubes (9-NT) with an inner diameter of 18 nm, wall thickness of 3 nm, and length of several micrometers. [36] Structural analysis revealed that in 9-NT, 9…”
Section: Cleavage Of a Nitrobenzyl Groupmentioning
confidence: 99%
“…33 The relationship between the inner diameters of nanotubes and guest sizes sensitively affect the features of encapsulation, diffusion/transportation, stabilization, release, and refolding of guest substances including proteins. 35,36,40,51,52,114,115 A typical example was shown by the fact that optimized inner surfaces of SMNTs and the exterior functionalities of a guest protein enable some SMNTs to behave as artificial molecular chaperone. 35,36 Moreover, one recent outstanding advance in new functions that will take place in the interior nanospace is the utilization of a multiwalled LNT as a sample fixation substrate for transmission electron microscopy (TEM) computed tomography (CT).…”
Section: Interior Nanospacementioning
confidence: 99%
“…With a targeting substance except for those denatured proteins, Kameta and Akiyama have recently reported attractive chaperone-like phenomena that cause duplex formation of short nucleotides. 52 Utilization of macromolecular crowding and confinement, 510 mismatch-binding ligands, 511 supramolecular nanocavities, 512 or silica mesopores 513 has been needed for the duplex formation so far. However, a successive series of encapsulation, subsequent acceleration of reaction, and release of final product occurs in the action fields of the newly developed, photoresponsive and shrinkable BANTs.…”
Section: Protein Refolding and Solubilizationmentioning
confidence: 99%